A micromechanics-based degradation model for composite progressive damage analysis. (July 2016) - Zhang, Jianyu; Zhou, Longwei; Chen, Yuli; Zhao, Libin; Fei, Binjun
A new material degradation model only with fundamental material properties required is proposed for composite progressive damage analysis based on micromechanics. For different failure modes, the effects of fiber and/or matrix damage on the composite material properties are explored, from which the material degradation factors for these failure modes are deduced. The material degradation model is then implemented for progressive damage analyses, using user subroutines in the commercial code ABAQUS®, accompanying with a modified Hashin type failure criterion and finite element models for six commonly used double-lap composite bolted joints with various layups, geometry dimensions, and fasteners. The numerical predictions of failure loads, failure patterns, and load–displacement curves are compared with results obtained from static tests and further ultrasonic C-scan detection. Good agreements between numerical failure predictions and experimental outcomes indicate the effectiveness and suitability of the proposed model for progressive damage analyses of composite bolted joints.